Linear Speed Regulation Design of Three-platform Operating Device Based on PWM Control for Catenary Overhaul Vehicle - NIU Xuexin; CHEN Hao; LYU Maoyin; YANG Xiao (Kongzhi Yu Xinxi Jishu)
In view of the defect that the existing imported three-platform operation device of DPT catenary overhaul vehicle can only operate at constant speed, it adopted PWM control technology to develop a domestic self-developed system with adjustable operation speed. In order to establish the linear relationship between the actual operating speed of the three-platform operation device and the speed regulator potentiometer, non-linear relationship between the output current of proportional solenoid valve and the hydraulic flow rate is processed in segments and the theoretical error is calculated. The start-stop buffer and start-up pulse control strategy are adopted to alleviate the start-up overshoot attenuation time of the second-order system response of the three-platform operation device. The simulation and experiment results show that the self-developed three-platform operation device has good performance in field operation, and the speed regulation error is less than 5%, which meets the engineering application requirements.